2010
DOI: 10.1167/iovs.09-3999
|View full text |Cite
|
Sign up to set email alerts
|

ACS67, a Hydrogen Sulfide–Releasing Derivative of Latanoprost Acid, Attenuates Retinal Ischemia and Oxidative Stress to RGC-5 Cells in Culture

Abstract: Purpose. To determine the neuroprotective properties of a latanoprost acid derivative (ACS67) that donates the gas hydrogen sulfide (H(2)S). Methods. Ischemia to the rat retina was induced by elevation of intraocular pressure. Electroretinograms (ERGs) were recorded and the retinas analyzed 2 days later by immunohistochemistry, Western blot analysis, and RT-PCR. Hydrogen peroxide (H(2)O(2)) was used to impose an insult on RGC-5 cells in culture. The nature of the insult to cultures was quantified by the resazu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 62 publications
3
41
0
Order By: Relevance
“…The H 2 S-cysteine-GSH connection has been documented often in the biomedical literature (26,59,93,94,141,147,158). Five factors are currently considered to contribute to the H 2 Sstimulated increase in intracellular GSH levels: (i) enhancement of cellular glutamate uptake (194), (ii) a H 2 S-induced increase in the level of gamma-glutamylcysteine synthetase and cystine transporter activity in the cell (94) (iii), reduction of cystine into cysteine by H 2 S in the extracellular space, and transport of cysteine into cells by the cysteine transporter (93), (iv) H 2 S stimulation of nuclear transcription factor Nrf2, which in turn upregulates GSH synthesis and transport (9,26), and (v) a decrease in the activity of GSH-catabolizing enzymes (184).…”
Section: Fig 2 Enzymatic Synthesis Of Hydrogen Sulfide (H 2 S)mentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 S-cysteine-GSH connection has been documented often in the biomedical literature (26,59,93,94,141,147,158). Five factors are currently considered to contribute to the H 2 Sstimulated increase in intracellular GSH levels: (i) enhancement of cellular glutamate uptake (194), (ii) a H 2 S-induced increase in the level of gamma-glutamylcysteine synthetase and cystine transporter activity in the cell (94) (iii), reduction of cystine into cysteine by H 2 S in the extracellular space, and transport of cysteine into cells by the cysteine transporter (93), (iv) H 2 S stimulation of nuclear transcription factor Nrf2, which in turn upregulates GSH synthesis and transport (9,26), and (v) a decrease in the activity of GSH-catabolizing enzymes (184).…”
Section: Fig 2 Enzymatic Synthesis Of Hydrogen Sulfide (H 2 S)mentioning
confidence: 99%
“…The slow-releasing H 2 S prodrug ACS67 (a latanoprostdithiolethione conjugate) was shown to attenuate retinal ischemic damage following experimental elevation of retinal pressure in rats, with ACS67 being more potent than latanoprost (147). The same authors found that ACS67 significantly attenuated hydrogen peroxide-induced damage to transformed neural precursor cells known to exhibit a number of characteristics associated with retinal ganglion cells (RGC).…”
Section: Cytoprotection and Pharmacological Conditioningmentioning
confidence: 99%
“…For instance, H 2 S can alter neurotransmitter release from tissues of the anterior uvea and retina and can exert a neuroprotective action in the retina. 10,[15][16][17]19,27,28 There is evidence that H 2 S can relax both isolated mammalian irides and posterior ciliary arteries.…”
Section: Hydrogen Sulfide and Intraocular Pressure 373mentioning
confidence: 99%
“…As performed in previous studies, 20 our ERG results for experimental groups were expressed as percent of these control values. Seven days after OH, amplitudes of the a-and b-waves and OPs were significantly decreased to 74, 29, and 27%, respectively (Fig.…”
Section: Calpain Inhibitor Snj-1945 Attenuated Degeneration and Dysfumentioning
confidence: 99%